UPAYA PENGEMBANGAN WAKAF UANG DI YOGYAKARTA (STUDI KASUS BMT BIF DAN BMT AL-IKHLAS) - Ibnu Kholil Utomo (EPI 16 UMY 111, 2016)

(untitled)
*111 This research is aimed at identifying the development of financial endowment organized by BMT (Sharisa microfinance institution) BIF and BMT Al-Ikhlas Yogyakarta as well as at identifying the strength, weakness, opportunity and threat faced by those aforementioned institutions. This research is based on the high potency is supported by the number of moslem living in Yogyakarta. The type of this research is qualitative research, in which the data were taken through interview and documentation study toward the management of BMT BIF and BMT Al-Ikhlas were compiled; such as socialization effort, education on financial endowment for society, amount of the financial endowment and its organization. The research result indicates that there are several obstacles faced by BMT BIF and BMT Al-Ikhlas; namely the lack of knowledge o financial endowment among the society of Yogyakarta, and some more internal and external obstacles. Keywords: Effort, Financial Endowment, Development